Avaliação de visualizadores de PACS em um centro de diagnóstico por imagem - Reale, Emerson Argolo (2021)
Introduction: Currently, PACS (Picture Archiving and Communication System) is widely used in diagnostic imaging services. Its use has brought many advantages, however, there are still some difficulties related to the transmission, archiving, retrieval of images, as well as some problems in the operation of viewers at workstations by the radiologist. Objective: To develop a methodology for evaluating PACS viewers to detect possible failures in their functioning and verify the correlation with the time taken to interpret the exams and with the degree of user satisfaction. Methods: This research consisted of a detailed evaluation of four PACS viewers in a diagnostic imaging center. A method for evaluating PACS viewers with 3 data collection instruments was established. First, an evaluation form with data from users, radiologists. Then, an evaluation scenario was set up, simulating the real situation of the radiologist in the interpretation of imaging tests to prepare the report. After the conclusion of this scenario, a satisfaction questionnaire was used with several items to be answered by the radiologist, referring to the experience with the viewers. Results: The PACS viewers were used by 5 users, radiologists, from the diagnostic center. The results obtained showed that there was no statistically significant difference in the time spent interpreting the exams in the evaluated viewers. There was a good level of general satisfaction in the experience with the PACS, although with a lower level in some evaluated tools. Strong and negative correlation was found between the users' age, graduation time, time working as a radiologist, and the degree of satisfaction with PACS viewers. Conclusion: The proposed methodology for evaluating the viewers was able to identify the failures during its use and made it possible to establish correlations between them, the interpretation time of the exams and the users' satisfaction.